2019
DOI: 10.1213/ane.0000000000003718
|View full text |Cite
|
Sign up to set email alerts
|

Use of the American College of Surgeons National Surgical Quality Improvement Program Surgical Risk Calculator During Preoperative Risk Discussion: The Patient Perspective

Abstract: The ACS Calculator may be of particular benefit to high-risk surgical populations by providing realistic expectations of outcomes and recovery. Use of this tool may also provide motivation for patients to participate in risk reduction strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 27 publications
1
43
0
Order By: Relevance
“…In general, patients request structural and individualised information from HCPs prior to surgery, and not solely regarding physical exercise [12]. It has been shown that patients at high risk tend to underestimate their risk of postoperative morbidity, but when made aware, the majority would consider taking action to preoperative optimisation [31]. Clinician-patient communication has shown to have positive effects on outcomes such as patient knowledge and understanding, adherence and better self-care abilities [32].…”
Section: Discussionmentioning
confidence: 99%
“…In general, patients request structural and individualised information from HCPs prior to surgery, and not solely regarding physical exercise [12]. It has been shown that patients at high risk tend to underestimate their risk of postoperative morbidity, but when made aware, the majority would consider taking action to preoperative optimisation [31]. Clinician-patient communication has shown to have positive effects on outcomes such as patient knowledge and understanding, adherence and better self-care abilities [32].…”
Section: Discussionmentioning
confidence: 99%
“…Online risk calculators, mobile device applications, and automated predictive analytic platforms can be easily accessed to accomplish these goals. [1][2][3][4] However, these models often ignore intraoperative data and thereby miss potentially important opportunities to generate updated predictions that can further inform future decisions regarding postoperative triage, surveillance for complications, targeted preventative measures (e.g., renal protection bundles for patients at high risk for acute kidney injury [AKI], and continuous cardiorespiratory monitoring for patients at high risk for cardiovascular complications).…”
Section: Introductionmentioning
confidence: 99%
“…However, the use of visual decisionmaking aids is associated with greater patient knowledge and satisfaction with their decision to have surgery [15]. NSQIP is a free and easy to use tool which has the potential to address this need for a wide range of operations [16]. There is currently a paucity of data regarding its validity in gynae-oncology, highlighting the importance of analysing NSQIP further in this field.…”
Section: Discussionmentioning
confidence: 99%